2024
DOI: 10.1002/adhm.202303785
|View full text |Cite
|
Sign up to set email alerts
|

Pump‐Less, Recirculating Organ‐on‐Chip (rOoC) Platform to Model the Metabolic Crosstalk between Islets and Liver

Aleksandra Aizenshtadt,
Chencheng Wang,
Shadab Abadpour
et al.

Abstract: Type 2 diabetes mellitus (T2DM), obesity, and metabolic dysfunction‐associated steatotic liver disease (MASLD) are epidemiologically correlated disorders with a worldwide growing prevalence. While the mechanisms leading to the onset and development of these conditions are not fully understood, predictive tissue representations for studying the coordinated interactions between central organs that regulate energy metabolism, particularly the liver and pancreatic islets, are needed. Here, a dual pump‐less recircu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 127 publications
(187 reference statements)
0
1
0
Order By: Relevance
“…Our data revealed that palmitate amplifies insulin section in both human primary islets and SC-islets. To this end, the SC-islets would be suitable for obese modeling, and our previous work has evaluated palmitate’s long-term effects on SC-islets ( Aizenshtadt et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data revealed that palmitate amplifies insulin section in both human primary islets and SC-islets. To this end, the SC-islets would be suitable for obese modeling, and our previous work has evaluated palmitate’s long-term effects on SC-islets ( Aizenshtadt et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to accurately reflect the physiology of human islets, it is crucial to meticulously compare the utilization and responses of SC-islets to various nutrients with those of human primary islets ( Beydag-Tasöz et al, 2023 ; Jensen and Little, 2023 ). For example, we have coupled SC-islets and SC-liver organoids in a recirculating organ-on-chip (rOoC) platform and generated a metabolic crosstalk model between islets and liver ( Aizenshtadt et al, 2024 ). To provide insights before SC-islets spread into downstream utilization for drug testing and development, this study developed a merged protocol based on recently developed SC-islets differentiation protocols ( Hogrebe et al, 2020 ; 2021 ; Mahaddalkar et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to implement more complex in vitro systems to study human physiology and pathophysiology, as well as disease progression that allow for the study of organ crosstalk and interaction. The development of human liver [37][38][39][40][41][42][43] pancreatic islets [44][45][46][47][48] , and coupled [49][50][51][52] biomimetic microphysiology systems (MPS) that can reflect the genomic, as well as environment and lifestyle heterogeneity offer an important opportunity to recapitulate the heterogeneity of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to accurately reflect the physiology of human islets, it is crucial to meticulously compare the utilization and responses of SC-islets to various nutrients with those of human primary islets (Beydag-Tasöz et al, 2023;Jensen and Little, 2023). For example, we have coupled SC-islets and SC-liver organoids in a recirculating organ-on-chip (rOoC) platform and generated a metabolic crosstalk model between islets and liver (Aizenshtadt et al, 2024). To provide insights before SC-islets spread into downstream utilization for drug testing and development, this study developed a merged protocol based on recently developed SC-islets differentiation protocols (Hogrebe et al, 2020;Mahaddalkar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%